Ultrastructural features of spermatozoa and their phylogenetic application in Zaprionus (Diptera, Drosophilidae) - Rego, Letícia do Nascimento Andrade de Almeida [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; Azeredo-Oliveira, Maria Tercília Vilela de [UNESP]; Madi-Ravazzi, Lilian [UNESP] (Taylor & Francis, 2016)
The genus Zaprionus consists of approximately 60 species of drosophilids that are native to the Afrotropical region. The phylogenetic position of Zaprionus within the Drosophilidae family is still unresolved. In the present study, ultrastructural features of spermatozoa of 6 species of Zaprionus as well as the species Drosophila willistoni and Scaptodrosophila latifasciaeformis were analyzed. The ultrastructure revealed that the species have the same flagellar ultrastructure. Two mitochondrial derivatives, one larger than the other, close to the axoneme were present, primarily in D. willistoni (subgenus Sophophora). Except for Z. davidi and Z. tuberculatus, the analyzed species had paracrystalline material in both mitochondrial derivatives. Moreover, the testes showed 64 spermatozoa per bundle in all of the species. In the cluster analysis, 6 Zaprionus species were grouped closely, but there were some incongruent positions in the cladogram. The results indicated that sperm ultrastructure is an important tool for elucidating the phylogeny and taxonomy of insects.
Keywords: Mitochondrial derivatives; Spermatogenesis cystic; Spermiogenesis